Five year risk of progression of primary angle closure suspects to primary angle closure: a population based study. Issue 4 (1st April 2003) - Thomas, R; George, R; Parikh, R; Muliyil, J; Jacob, A
Abstract : Aim: To report progression of primary angle closure suspects (PACS) to primary angle closure (PAC) at the 5 year follow up of a population based sample. Methods: 82 of 118 PACS who could be contacted and 110 randomly selected normals from a population based survey in 1995 were invited for a follow up examination in 2000. Progression to PAC was based on the development of raised IOP or synechiae in a PACS. Results: 50 of the 82 PACS contacted were examined. 11 (22%; 95% CI 9.8 to 34.2) developed PAC (seven synechial and four appositional); all were bilateral PACS. Two of 50 people previously diagnosed as PACS were reclassified as normal. One person among the 110 normals progressed to PAC. The relative risk of progression among PACS was 24 (95% CI 3.2 to 182.4). There was no significant difference in axial length, anterior chamber depth, or lens thickness between those who progressed and those who did not. None of the patients developed optic disc or field damage attributable to angle closure. One angle closure suspect was diagnosed to have normotensive glaucoma. Conclusion: In this population based study of PACS the 5 year incidence of PAC was 22%; none developed functional damage. Bilateral PACS was a clinical risk factor for progression.